(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
Hospital management is crucial in the management of textiles, ensuring functionality, durability, biosafety, and infection control, directly impacting patient safety, operational efficiency, and the sustainability of healthcare services. The objective of this study is to demonstrate how the implementation of structured practices for textile conservation and linen management in hospital laundries contributes to greater material durability, operational efficiency, patient safety, reduction of environmental impacts, and sustainability. The methodology was based on a narrative literature review. The results highlight that the correct interpretation of care labels, the implementation of appropriate hygiene protocols, and efficient linen management are determining factors in extending product lifespan, reducing institutional costs, and minimizing environmental impacts. It is concluded that integrated and interdisciplinary management, aligned with technical standards and rigorous protocols, represents a strategic investment that yields operational, economic, and environmental gains, in addition to contributing to humanized care and excellence in assistance.